Purcell-enhanced single photons at telecom wavelengths from a quantum dot in a photonic crystal cavity - Catherine L. Phillips; Alistair J. Brash; Max Godsland; Nicholas J. Martin; Andrew Foster; Anna Tomlinson; René Dost; Nasser Babazadeh; Elisa M. Sala; Luke Wilson; Jon Heffernan; Maurice S. Skolnick; et al. (Scientific Reports, 2024)
Abstract Quantum dots are promising candidates for telecom single photon sources due to their tunable emission across the different low-loss telecommunications bands, making them compatible with existing fiber networks. Their suitability for integration into photonic structures allows for enhanced brightness through the Purcell effect, supporting efficient quantum communication technologies. Our work focuses on InAs/InP QDs created via droplet epitaxy MOVPE to operate within the telecoms C-band. We observe a short radiative lifetime of 340 ps, arising from a Purcell factor of 5, owing to integration of the QD within a low-mode-volume photonic crystal cavity. Through in-situ control of the sample temperature, we show both temperature tuning of the QD’s emission wavelength and a preserved single photon emission purity at temperatures up to 25K. These findings suggest the viability of QD-based, cryogen-free C-band single photon sources, supporting applicability in quantum communication technologies.